Low genetic diversity in the locus encoding the Plasmodium vivax P41 protein in Colombia's parasite population (2014)
Background: The development of malaria vaccine has been hindered by the allele-specific responses produced by some parasite antigens' high genetic diversity. Such antigen genetic diversity must thus be evaluated when designing a completely effective vaccine. Plasmodium falciparum P12, P38 and P41 proteins have red blood cell binding regions in the s48/45 domains and are located on merozoite surface, P41 forming a heteroduplex with P12. These three genes have been identified in Plasmodium vivax and share similar characteristics with their orthologues in Plasmodium falciparum. Plasmodium vivax pv12 and pv38 have low genetic diversity but pv41 polymorphism has not been described.Results: Similarly to other members of the 6-Cys family, pv41 had low genetic polymorphism. pv41 3′-end displayed the highest nucleotide diversity value; several substitutions found there were under positive selection. Negatively selected codons at inter-species level were identified in the s48/45 domains; p41 would thus seem to have functional/structural constraints due to the presence of these domains.Methods. The present study was aimed at evaluating the P. vivax p41 (pv41) gene's polymorphism. DNA sequences from Colombian clinical isolates from pv41 gene were analysed for characterising and studying the genetic diversity and the evolutionary forces that produced the variation pattern so observed.Conclusions: In spite of the functional constraints of Pv41 s48/45 domains, immune system pressure seems to have allowed non-synonymous substitutions to become fixed within them as an adaptation mechanism; including Pv41 s48/45 domains in a vaccine should thus be carefully evaluated due to these domains containing some allele variants. © 2014Forero-Rodríguez et al.; licensee BioMed Central Ltd.